Studies on phytoplankton productivity in Kavaratti Atoll, Lakshadweep - Suresh, V R; Mathew, K J (Indian Journal of Fisheries, 2011)
Productivity contribution of phytoplankton in Kavaratti Atoll, Lakshadweep, wasstudied for one year (Jan, to Dec, 1989) using light and dark bottle method. Grossproduction (mg C/m%r) varied between 0.62±0.01 and 6.0±2.5 and net productionbetween 0.2±0.13 and 1.46±0.85. Gross production showed seasonal variations witha fall during monsoon months (June-September). Productivity appeared highlyvariable and limited by salinity as well as light conditions.